Hadith #4309 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu al-Tufayl, 'Amir bin Wathla; Farat bin Abi 'Abdur Rahman فرات بن أبي عبد الرحمن القزاز; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
The Prophet (ﷺ) said: Leave the Abyssinians alone as long as they leave you alone, for it is only the Abyssinian with short legs who will seek to take out the treasure of the Ka’bah.
Grade: Hasan